(3GdTYQGhjs (3GdbjKGQI GdEjeGfjIs - (3Ydj, ceGd eMeOs ((3GdbGgQIs (3GdeWHYI GdYQHjI GdMOjKIs, 1989)
(3jJfGhd GdcJGH MjGI GdEeGe eMeO eJhdj GdTYQGhj cfLe SGWY aj SeGA GdOYhI GdESdGejI HGdEVGaI dYQV eLehYI ef ehGbaI JLGI GdMQjI hHYV GdbVGjG GdLOdjI eKd Gdjhe GdBNQ hGdSGYI hYdGeJgG GdcHQj hZjQgG, CjVG jYQV GdcJGH ehba GdEeGe ef HYV GdTNUjGJ GdYGeI hGdadGSaI eKd Rcj fLjH eMehOs
Keywords: (3eMeO eJhdj GdTYQGhjs; (3GdESdGe hGdYdes; (3GdESdGe hGdadSaIs; (3GdESdGes -- (3JQGLes; (3GdeUQjhfs; (3HQGeL GdJdjaRjhfs